CLOUD CATALOG DAN INTEGRASI DIGITAL MARKETING UMKM - Alfirah; Gustiana, Zelvi; Hadi Elyas, Ananda (Jurnal Pengabdian Masyarakat, 2023)
DW Food Court (DFC) is located in Glugur City, West Medan District. Currently, DFC consists of 10 culinary MSMEs run by students who are still actively studying at Dharmawangsa University. As science and technology develop, understanding the cloud catalog and MSME digital marketing features aims to collect data related to the variety of MSME products and the number of students who are entrepreneurs. However, it is considered necessary to provide business assistance supported by training, capital assistance/business facilities, and of course requires a digitalization system that supports operations in marketing their products, both conventionally and digitally. However, of all members of the DW Food Court (DFC), still < 25% are business members. A maximum proposal summary of 500 words containing problems, solutions and output targets to be achieved in accordance with each community service scheme. The summary also contains a careful and brief description of the proposed activity plan. which already has digital marketing features (website, social media, marketplace, cloud catalog) to promote its products. Most DFC members are still comfortable using conventional media, such as waiting for buyers to come to the sales stand and participating in MSME bazaars. For this reason, it is hoped that this Community Service activity will be able to expand the marketing network and increase sales volume on a regular basis and with a digitalization system. This activity was carried out by lecturers and students from the Faculty of Information and Computer Engineering (FTIK) and the Faculty of Economics and Business (FEB) at Dharmawangsa University. The solutions and output targets offered include products and services, such as training modules and survey forms (pre/post test), business menu designs, business profile videos, social media accounts (Instagram), websites (market.dharmawangsa@ac.id and uptti2pb.dharmawangsa@ac.id), activity documentation, online news publications and publications.